2015
DOI: 10.1089/chi.2014.0090
|View full text |Cite
|
Sign up to set email alerts
|

A Classroom-Based Physical Activity Intervention for Urban Kindergarten and First-Grade Students: A Feasibility Study

Abstract: CHAM JAM significantly increased school-based PA among kindergarten and first-grade students in inner-city schools. This approach holds promise as a cost-effective means to integrate the physical and cognitive benefits of PA into high-risk schools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 46 publications
1
31
0
Order By: Relevance
“…Interventions contained an average of 3. 18 or an audio CD and CD player 65 . Intervention effects on outcomes…”
Section: Behaviour Change Techniques (Bcts) Used In Interventionsmentioning
confidence: 99%
“…Interventions contained an average of 3. 18 or an audio CD and CD player 65 . Intervention effects on outcomes…”
Section: Behaviour Change Techniques (Bcts) Used In Interventionsmentioning
confidence: 99%
“…Two interventions used a standardized video for MI [77,83]. Seven researcherdriven interventions did not provide training [53,63,64,67,68,75,79] and four did not report if there was any training [52,76,82,84]. The duration of the training varied from 30 min [54] to a full school day [50,60,61,78].…”
Section: Researcher-drivenmentioning
confidence: 99%
“…About one-fourth of the researcher-driven interventions did not measure fidelity [52,53,63,64,67,69,72,76,82,84], and of those that measured it, about half studies reported that the intervention was delivered as intended [50,51,58,61,62,65,68,70,74,80,81,83,85]. The measures used for fidelity varied between teacher logs [54-56, 58, 73, 75, 77], direct observation [51,57,65,68,74], activity monitors [62,70,80], meetings or ending surveys [60,86], or a combination of measures [50,59,61,66,78,79].…”
Section: Researcher-drivenmentioning
confidence: 99%
“…Multilevel models were used to identify significant predictors for differences in step count changes for intervention and control groups [ 7 , 30 , 57 , 58 ]. A feasibility study on classroom-based physical activity was analysed, adjusting for within cluster correlation at three different levels, namely student, classroom and school, using random effects for school, classroom and subject and assuming fixed effects for grade, gender, outdoor recess and physical education [ 7 ]. The effectiveness of goal manipulation along with social comparison feedback within an intervention have also been tested using multilevel models [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Different types of activity program are used to target populations with differing characteristics. Several systematic reviews discuss the effectiveness of school-based physical activity programs [ 4 7 ]. For example, the systematic review in [ 8 ] suggests that there is a positive effect on behavior and physical status resulting from ongoing school-based physical activity interventions.…”
Section: Introductionmentioning
confidence: 99%